2017
DOI: 10.1007/s11284-017-1517-5
|View full text |Cite
|
Sign up to set email alerts
|

Broad scale variation in seagrass benthic macrofaunal assemblages along the coast of Japan

Abstract: Broad scale studies in seagrass benthic macrofauna are important for future regional marine conservation. We examined spatial variation in the community structure of seagrass‐associated benthic macroinvertebrates collected by sediment coring in 2010 at six seagrass sites of Japan covering the latitudinal range of 24°–43°N. Total species richness and ES(50) at site level did not show clear site variations and relationship with latitude. At core level, site variations of mean species richness, ES(50), Simpson di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Our study contributes to a growing number of existing beta-diversity estimates for seagrassassociated animals, mostly infauna living in the sediments rather than on the blades (Barnes 2013a, Boy e et al 2017, Cullain et al 2017, Leopardas et al 2018). In these studies, observed community structure tended to be variable across regional scales, though these differences, similar to our findings, were often driven by community composition, rather than differences in species richness.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our study contributes to a growing number of existing beta-diversity estimates for seagrassassociated animals, mostly infauna living in the sediments rather than on the blades (Barnes 2013a, Boy e et al 2017, Cullain et al 2017, Leopardas et al 2018). In these studies, observed community structure tended to be variable across regional scales, though these differences, similar to our findings, were often driven by community composition, rather than differences in species richness.…”
Section: Discussionmentioning
confidence: 79%
“…, Leopardas et al. ). In these studies, observed community structure tended to be variable across regional scales, though these differences, similar to our findings, were often driven by community composition, rather than differences in species richness.…”
Section: Discussionmentioning
confidence: 99%
“…For infauna, it was difficult to obtain animal samples using a 0.5 mmsieve because the samples contained too fine sediment particles. Therefore, we followed the protocols in previous studies (e.g., Leopardas et al, 2018) using 1 mm-sieve for infauna sampling. All the belowground parts found in the core samples were sorted, placed in small aluminum bags, and dried in a drying oven at 60 C for 48 hr or until completely dried (i.e., below-ground biomass).…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…Galindon et al (2018) compare the status of biodiversity in forests in limestone quarries in different sub-regions of the Philippines with different management histories (reforestation). Leopardas et al (2018) use data from the Japanese 'Monitoring Sites 1000' program to examine broad-scale variations in marine biodiversity patterns in seagrass benthic communities. Finally, Fang et al (2018) make special reference to the implications of classification methods used in different studies and interactions with human activities for ecosystem conservation and restoration in their review of ecological connectivity between land and sea.…”
Section: Editorialmentioning
confidence: 99%